Draft genome sequence of Yersinia pestis strain 2501, an isolate from the great gerbil plague focus in Xinjiang, China - Sun, Surong; Yang, Xianwei; Yuan, Yanting; Dai, Xiang; Yan, Yanfeng; Cao, Hanli; Luo, Tao; Guo, Rong; Wang, Xinhui; Song, Yajun; Yang, Ruifu; Zhang, Yujiang; et al. (Journal of bacteriology, 2012)
We deciphered the genome of Yersinia pestis strain 2501, isolated from the Junggar Basin, a newly discovered great gerbil plague focus in Xinjiang, China. The total length of assembly was 4,597,322 bp, and 4,265 coding sequences were predicted within the genome. It is the first Y. pestis genome from this plague focus.